Conformal multiple input multiple output antenna array for wireless avionics intra‐communications system in aircraft cabin. Issue 10 (2nd July 2022) - Fan, Xianghui; Li, Shining; Ma, Xiao‐Yu; Pang, Zi‐Yu; Huang, Guan‐Long; Chen, Rui‐Sen
Abstract: This article presents a conformal multiple input multiple output (MIMO) antenna array for wireless avionics intra‐communications (WAIC) system application. The MIMO array consists of five probe‐fed rectangular patch antennas, which are conformal with a hemispherical platform. Each antenna element of the antenna array radiates toward different angles, forming a wide signal coverage in aircraft cabin. To further enhance isolation between close‐spacing antenna elements and improve MIMO performance, metallic slots are included in the ground plane. The MIMO array is analyzed with design details and a prototype is fabricated for verification. Experimental results show that the MIMO array has good isolation and radiation characteristics in the WAIC band of 4.2–4.4 GHz. The low‐cost and conformal configuration with compact size of the designed MIMO array make it a promising candidate for future WAIC applications.